SIFAT VENIR DAN KAYU LAPIS BEBERAPA JENIS KAYU INDONESIA - Suwandi Kliwon; M I Iskandar; Paribotro Sutigno (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
This report deals with peeling, physical and mechanical properties of veneer and some physicai and mechanical properties of plywood (triply) of 16 wood species from East Kalimantan and 1 species from West Java. The logs of all wood species tested could be peeled without heating or steaming. Veneer of 0.9 mm and 1.5 mm in thickness could be peeled at cutting angles between 89° and 92°.The yield of green veneer was 46. 7% and the average shrinkage was 10. 7% with a minimum of 5.9% (jabon) and maximum of 13.9% (merembung). Thickness swelling from oven dry to air dry varied between 2. 7% (medang tanduk) and 3.9%(nyatoh) with an average of 3.4%.The bonding strength of plywood made of 5 wood species (29. 4%) was in complience with the Indonesian standard for type II or water resistant, 11 wood species (64. 7%) with Japanese standard and 6 species (35.3%) with German standard.The average thickness reduction due to pressing pressure was 0.23 mm with minimum of 0. 07 mm (buah sayap) and maximum of 0.44 mm (merant imerah).The specific gravity of wood used in this experiment varied between 0.30 (merembung) and 0. 80 (kapur). The specific gravity of plywood ranged from 0.46 (jabon) to 0.89 (medang tanduk).The average values of bending strength parallel and perpendicular to grain of 3 mm triply were 1221.29 kg/cm2 and 603.68 kg/cm2, respectively. The tensile strength parallel and perpendicular to grain were 625.95 kg/cm2 and 539.93 kg/cm2, respectively. The average values for bending strength parallel and perpendicular to grain of 4 mm triply were 1096.31 kg/cm2 and 398.8 kg/cm2, respectively. The tensile strengths parallel and perpendicular to grain were 696.46 kg!/cm2 and 443.95 kg/cm2, and 443.95 kg/cm2. respectively.